Influence of Date of Transplanting and Level of Nitrogen on the Yield of Nizershail Rice Grown in Boro Season - Md. Abdus Salam; Urmi Rani Das; Md. Moshiur Rahman; Swapan Kumar Paul (Turkish Journal of Agriculture: Food Science and Technology)
Proper nitrogen (N) management is vital for gaining potential yield benefits of a variety. Adjusting transplanting time enables the plant taking benefit from natural conditions favorable for its growth. In light of these, an investigation was carried out in the Boro season at the Agronomy Field Laboratory, Bangladesh Agricultural University from November 2022 to April 2023 to investigate the impact of various transplanting dates and N levels on the yield of Nizershail rice. The study involved four dates of transplanting viz. 16 December, 31 December, 15 January, 30 January and four nitrogen (N) levels viz. 0, 50, 100 and 150% of the recommended dose (RD) of N from urea where the recommended dose was 90 kg urea per ha. The trial was replicated thrice using Randomized Complete Block Design (RCBD). Results showed that the tallest plant, the uppermost grains/panicle and 1000 grains weight were detected in 16 December transplanting and the maximum grain yield was observed in 31 December transplanting. For N, total tillers and effective tillers/hill, grains/panicle, the highest grain and straw yields were found from 100% RD of N and the highest panicle length and sterile spikelets/panicle were found from 150% RD of N. In interactions, the maximum effective tillers/ hill and straw yield were observed from 100% RD of N in combination with 15 January transplanting. The maximum 1000 grains weight and the grain yield were obtained from 100% RD of N in combination with 16 December transplanting. From the result, it may be assumed that to get the maximum yield of Nizershail rice in Boro season could be transplanted between 16 December to 15 January with 100% RD of N from urea.